2017
DOI: 10.1186/s12912-017-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan and associated factors of peripheral intravenous Cannula among infants admitted in public hospitals of Mekelle City, Tigray, Ethiopia, 2016

Abstract: BackgroundPeripheral Intravenous cannula (IV) is the most common vascular access device used to administer medications with the exception of medication or fluid with high or low PH or hyperosmolarity which may cause severe damage to small veins. The insertion of a peripheral intravenous cannula in newborn infants can be difficult. Appropriate veins with sufficient capacity to insert a cannula become less available throughout the hospital stay. Once a peripheral intravenous cannula is inserted, it is desirable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Optimising PIVC insertion and lowering the PIVCs complication rate is crucial for optimising care in children. Only a few studies have addressed this issue, even though PIVC use is a very common practice 8‐13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimising PIVC insertion and lowering the PIVCs complication rate is crucial for optimising care in children. Only a few studies have addressed this issue, even though PIVC use is a very common practice 8‐13 …”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on paediatric populations found that prolonged use of PIVCs, younger age and the administration of drugs through the catheter increased the risk of phlebitis 8 . PIVC insertion site, patient age and the experience of the staff member inserting the line affected PIVC lifespan 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…PIVCs had higher success rates when inserted in the cephalic vein in the proximal forearm under USG techniques or the antecubital fossa 109,123 and a longer life span when inserted into the arm compared to scalp, hand, or leg insertion sites. 33 CVAD insertion via the axillary vein using USG techniques resulted in fewer insertion attempts and significantly shorter time to guidewire insertion and time to cannulation. 78 Similarly, CVAD insertion in the subclavian vein was associated with shorter median puncture time, less insertion attempts, and significantly less guidewire misplacement compared to insertion via the infraclavicular approach.…”
Section: Recommendations For Insertion Insertion Locationsmentioning
confidence: 99%
“…This study revealed that the proportion of short life span of peripheral intravenous catheter was 52.8% (94) and of this proportion, 37.6% (67) catheters were removed within 24 hr. [6] Complications of central venous catheter and peripheral intravenous catheter are totally different so direct comparison is not possible so, in our study we had first divided their particular complications in three group like major , intermediate , and minor complication in which each category contains different type of complication pertinent to type of intravenous catheter used. In study of M. Jha, and Sunil Kumar.…”
Section: Discussionmentioning
confidence: 99%